Petroleum biotechnology developments and perspectives - Vazquez-Duhalt, Rafael.; Quintero Ramirez, Rodolfo, 1954- (Studies in surface science and catalysis, 2004)
This book is one of a kind in the field of petroleum biorefining and biological upgrade of petroleum; it presents a critical review as well as an integrated overview of the potential biochemical processes, bridging the gap between academia and industry. It addresses todays demanding production challenges, taking into account energy efficient and environmentally friendly processes, and also looks at the future possibility of implementing new refinery systems. Suitable for those practitioners the petroleum industry, students and researchers interested in petroleum biotechnology. * Covers a new application field for biotechnology * Looks at innovative processes for the petroleum industry * Presents examples of modern environmental processes.